179PPostoperative Adjuvant transarterial chemoembolization versus surgery alone for resected hepatocellular carcinoma: A propensity-score matching study. (24th November 2019) - Chen, M; Cao, J; Pan, L; Zhang, B; Cai, X
Abstract: Background: Whether postoperative adjuvant transarterial chemoembolization (PA-TACE) can prolong overall survival (OS) in patients with resected hepatocellular carcinoma (HCC) remains confusion. We aimed to assess and compare the efficacy of PA-TACE and surgery alone in patients with resected HCC. Methods: Data from patients who underwent surgery were selected and collected for retrospectively analysis. A propensity-score 1:1 matching analysis was performed. The overall survival was analyzed by the Kaplan-Meier method, and survival outcomes for patients who underwent PA-TACE were compared with those who underwent surgery alone. Results: A total 286 patients (PA-TACE vs surgery alone, 143:143) were identified and selected after a propensity-score 1:1 matching analysis. No significant difference was observed in each variable in the matched data. And, all Kaplan-Meier curves for overall survival between PA-TACE and surgery alone group showed significance before and after propensity score matching (P = 0.0065 and P < 0.001, respectively). Subgroup analysis showed patients with low BCLC stage and low albumin-bilirubin grade had a better overall survival in the PA-TACE group. Conclusions: Compared to surgery alone, PA-TACE could prolonger overall survival in patients with resected HCC, especially for who with low BCLC stage and/or low albumin-bilirubin grade. Legal entity responsible for the study: Xiujun Cai. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.